Analysis of the Influence of Internal Factors, External Factors and Bank Risk Factors on Rural Banks Performance - Ariyanto, Setia; Hadiprajitno, P. Basuki (Politeknik Siber Cerdika Internasional, 2024)
This study aims to prove the influence of bank internal factors, bank external factors and bank risk factors on the performance of Rural Banks (BPR). The research was conducted on BPRs that were categorized as BPRKU 3 with a core capital of at least IDR 50 billion at the end of 2021. The total sample of BPRKU 3 tested was 75 BPRs with a data period of 2016-2021. Data were analyzed using a quantitative approach using the SEM-PLS method through the SmartPLS 3 application. The results showed that internal factors had no effect on financial performance. While external factors have a positive and significant effect on financial performance while risk factors have a negative and significant effect on BPR financial performance.